2018
DOI: 10.1208/s12249-017-0939-2
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Aspasomes Against Rheumatoid Arthritis: Optimized Hydrogel Loaded Liposomal Formulation with In Vivo Evaluation in Wistar Rats

Abstract: Aspasomes of methotrexate with antioxidant, ascorbyl palmitate, were developed and optimized using factorial design by varying parameters such as lipid molar ratio, drug to lipid molar ratio, and type of hydration buffer for transdermal delivery for disease modifying activity in rheumatoid arthritis (RA). Aspasomes were characterized by drug-excipients interaction, particle size analysis, determination of zeta potential, entrapment efficiency, and surface properties. The best formulation was loaded into hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…A number of therapeutics, including paclitaxel (PTX) [105,106], doxorubicin (DOX) [107,108], methotrexate [109,110], cis-platin [111,112], curcumin [113,114], 5-fluorouracil [115,116], irinotecan [117,118], and nucleic acids [119,120], have been delivered via polymeric carriers [121] to cells. However, liposomes provide unique properties, as their charge, size, and surface properties can easily be tuned by selecting different ingredients of lipid mixture prior to the preparation of the liposomes.…”
Section: Biomedical Applications Of Folate-conjugated Liposomesmentioning
confidence: 99%
“…A number of therapeutics, including paclitaxel (PTX) [105,106], doxorubicin (DOX) [107,108], methotrexate [109,110], cis-platin [111,112], curcumin [113,114], 5-fluorouracil [115,116], irinotecan [117,118], and nucleic acids [119,120], have been delivered via polymeric carriers [121] to cells. However, liposomes provide unique properties, as their charge, size, and surface properties can easily be tuned by selecting different ingredients of lipid mixture prior to the preparation of the liposomes.…”
Section: Biomedical Applications Of Folate-conjugated Liposomesmentioning
confidence: 99%
“…The transdermal delivery efficacy of this system was assessed in vivo using an AIA rat model. [83] Application of the hydrogel for 12 days not only reduced the rat paw diameter, histopathological scores, and proinflammatory cytokine (TNF and IL-) levels but also decreased the side effects. Further studies are needed to establish the correlation and an optimized dosage regimen for the combination of MTX and ascorbyl palmitate.…”
Section: Transdermal Drug Delivery Systemsmentioning
confidence: 96%
“…Furthermore, the group treated with free MTX exhibited intermediate effects however, the group treated with free aspasome did not show to have an effect. The results demonstrated that drug-loaded therapeutically active carrier system presented a non-invasive controlled release transdermal formulation with good drug encapsulation, drug permeation rate, and showed a more effective therapeutic effect in treatment of RA than the drug alone [52].…”
Section: Bmmscsmentioning
confidence: 96%
“…The lipogels delivered a significant amount of drug through the skin than the hydrogel after 24 h. The constitution of lecithin showed to affect the skin permeability increasing the capability of the lipogel. Another study developed MTX aspasomes encapsulated into a hydrogel and tested in AIA model in Wistar rats [52]. Transdermal application of MTX-loaded aspasome hydrogel in model disease demonstrated a more significant decrease of rat paw diameter, tumor necrosis factor-alpha (TNF-α), interleukin (IL-1) β, cartilage damage, inflammation, pannus formation, and bone resorption when compared to arthritic control rats after 21 days.…”
Section: Bmmscsmentioning
confidence: 99%